KEBIJAKAN PEMBERDAYAAN MASYARAKAT DIFABEL IDIOT DI DESA KARANGPATIHAN KECAMATAN BALONG KABUPATEN PONOROGO JAWA TIMUR - Bambang Triono (JI@P, 2018)
Triono, 2018. “Policy Of Empowerment Of Idiot Diffable In The VillageRegion Of Balong District In Ponorogo East Java”. Public Administration,Slamet Riyadi University Surakarta. Theses. Unpublished.This study aims to analyze the empowerment of difabel idiot communityand encourage the empowerment of people with disabilities in the VillageKarangpatihan Balong District Ponorogo East Java Province. Theresearch method used qualitative approach, conducted in KarangpatihanVillage, Balong District, Ponorogo Regency, East Java, implemented fromOctober 2016 until January 2017. Data Collection Technique uses indepthinterview, documentation, and observation. Data analysis techniqueis done interactively. Result of the research: (1) The empowerment ofpeople with idiot difabel in Karangpatihan Village, Balong Sub-district,Ponorogo Regency, East Java, is done by village apparatus led by Headof Village in cooperation with Self-Help Group (KSM) Rumah HarapanBangkit in coaching and productive activities in form of cassette making,tasbeh And batik. To support the implementation of disabled communityeducation, Karangpatihan village government established early childhood"SMART. (2) Inhibiting factors are communication problems,communication difficulties between village apparatus, KSM administratorsand counterparts with persons with disabilities, the number of personswith disabilities with unequal counterparts, and availability of matmaterials dependent on other parties. In terms of implementation there isno regulation that can be used as a legal umbrella of suchimplementation. The encouraging factors include: community harmonyand living culture bergotongroyong, growing and berkengang communitycreativity to empower people with disabilities idiots, the willingness ofcitizens to make people with disabilities idiots become independentcommunities, the support of village and local government tools to supportcommunity activities difabel idiots, and the support of industry awarenessof the empowerment of people with disabilities.Keywords: Policy, Empowerment, Disability